Spread of ESBL-producing Escherichia coli in nursing home residents in Ireland and the Netherlands may reflect infrastructural differences. Issue 2 (October 2019) - Terveer, E.M.; Fallon, M.; Kraakman, M.E.M.; Ormond, A.; Fitzpatrick, M.; Caljouw, M.A.A.; Martin, A.; van Dorp, S.M.; Wong, M.C.; Kuijper, E.J.; Fitzpatrick, F.
Summary: A prevalence study in two nursing homes (one each in the Netherlands and Ireland) found four (11%) Dutch and six (9%) Irish residents colonized with 11 extended-spectrum beta-lactamase-producing Escherichia coli, 10 of which contained CTX-M-15. Four Dutch isolates, from three residents of the same ward, belonged to E. coli O25:H4, sequence type (ST) 131 and were part of the same cluster type by whole-genome sequencing. Four Irish residents on three different wards were colonized with an identical E. coli O89:H9, ST131, complex type 1478. Cross-transmission between three Irish wards may reflect differences in nursing home infrastructure, specifically communal areas and multi-bedded resident rooms.